Snap Ring Joint Design for Transmissions at Volvo Cars - Anderson Naveda, Leo (My University, 2020)
While the Volvo Car Corporation’s mission is to develop cars which will fulfill the customers expectations, the ergonomics of the technicians and mechanics is also taken into account. This study was carried out to optimize the design of the interface between the front left driveshaft and the gearbox differential to make it possible to assembly and disassemble with a snap fit. The study considers previous analytical studies in split rings as well as mathematical models in order to try to comprehend the forces acting on it during assembly and disassembly. Some parameters were tested in the workshop and later on in the Universal Testing Machine to obtain data from several different experiments. After having understood the model and having data to compare, a Finite Element Method was developed to be able to test further parameters. Once the model reassembled the tests previously carried out, a Design of Experiments was carried out using a response surface tool. Using this tool, the parameters which affect more the assembly and disassembly forces were identified. Results from the modeling don’t quite resemble the reality as the interface is very sensitive for contact and geometric imperfections but serve as a base to understand the most influential parameters. Finally, a new design was proposed based on all the previous experiments. Further recommendations for this topic are also given for alternative designs and what to avoid when designing a new ring.
Keywords: Snap ring; disassembly force; splined interface; driveshaft; snap design; ANSA; Contact modelling; Volvo Car Corporation; Differential gear; Retaining ring